2021
DOI: 10.1007/s13178-021-00564-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing Minds and Changing Laws: How New Zealand Sex Workers and Their Allies Shaped Decriminalisation in New Zealand

Abstract: Introduction This article provides insight into a rare instance of a collaborative governance approach to sex work that led to the decriminalisation, design and implementation of the sex work policy governance framework in New Zealand with the Prostitution Reform Act 2003. Methods Drawing on a sample of 17 interviews conducted between the years 2012 and 2019 in addition to associated archival material originating from government and non-govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Policy renewal should foreground the complex and multifaceted history of sex work in Amsterdam and consider the livelihood of sex workers, brothel owners, their representative organizations, and other residents of Amsterdam's city center over spatial arguments. The policy should actively engage with their voices and concerns, as other research has shown that collaborative governance can be a useful approach to improve the occupational health and safety of sex workers, while also improving local cohesion (Aroney, 2021;Blanchard et al, 2013;Kerrigan et al, 2015). Giving priority to the perspectives of sex workers and the community may potentially offer a more effective approach to achieving Project 1012's and other city regeneration plans' ostensible objectives of reducing crime and nuisance and enhancing living conditions for the people in Amsterdam.…”
Section: Discussionmentioning
confidence: 99%
“…Policy renewal should foreground the complex and multifaceted history of sex work in Amsterdam and consider the livelihood of sex workers, brothel owners, their representative organizations, and other residents of Amsterdam's city center over spatial arguments. The policy should actively engage with their voices and concerns, as other research has shown that collaborative governance can be a useful approach to improve the occupational health and safety of sex workers, while also improving local cohesion (Aroney, 2021;Blanchard et al, 2013;Kerrigan et al, 2015). Giving priority to the perspectives of sex workers and the community may potentially offer a more effective approach to achieving Project 1012's and other city regeneration plans' ostensible objectives of reducing crime and nuisance and enhancing living conditions for the people in Amsterdam.…”
Section: Discussionmentioning
confidence: 99%
“…There are now numerous examples from around the world of how peer networks of support have coalesced into successful political movements, ensuring sex workers’ advocate for their own priorities and tailor activities and programmes to their local risk environment with resulting reductions in their vulnerability to HIV and other adverse health and social outcomes [33,43–48]. In some cases, sex workers have forged powerful coalitions that contributed to changing national policy, such as the role of the New Zealand Prostitutes Collective in achieving decriminalization in Aotearoa New Zealand [49,50].…”
Section: Comprehensive Combination Preventionmentioning
confidence: 99%